Pertimbangan Hakim Dalam Menjatuhkan Sanksi Tindak Pidana Pencurian Ringan Perspektif Hukum Pidana Islam - Rahman Zulfadli Lubis; Zul Anwar Ajim Harahap; Ahmad Sainul (Jurnal El-Thawalib, 2022)
This article describes the judge's considerations in deciding the sanctions for minor theft from the perspective of Islamic Criminal Law. This type of research is normative. The legal materials of this research consist of primary and secondary legal materials in the form of Decision No: 8/Pid.C/TPR/2019/PN PSP, while secondary legal materials are in the form of books, journals and documents related to Islamic criminal law, data collection techniques with the case study method. In this study, the data analysis technique used is the legal hermeneutic analysis method. The results of this study indicate that in Islamic criminal law, theft can be referred to as ordinary theft when theft consists of four elements, namely the element of property taken secretly, the element of the item taken in the form of property, the element of the property being the property of another person and elements of malicious intent or against the law. While the decision No: 8/Pid.C/TPR/2019/PN PSP only consists of three elements that this crime is referred to as light theft, not ordinary theft. The punishment given is ta'zir punishment.